Upaya Penanganan Pembiayaan Bermasalah pada Akad Rahn di KSPPS BMT Mandiri Sejahtera Cabang Dukun - Adibah, Alda Naila; Habibi, M. Lutfillah (Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to explain the efforts to manage non-performing financing in the Rahn product at BMT Mandiri Sejahtera, Dukun Branch. Non-performing financing poses a significant challenge as it can disrupt the institution’s financial stability and reduce members’ trust. The study employs a qualitative descriptive method with data collected through interviews, observations, and documentation. The findings indicate that the main causes of non-performing financing stem from weaknesses in the initial survey and analysis process, as well as external factors such as members’ economic conditions and household issues. The handling efforts are carried out in stages through intensive supervision of ongoing financing, regular reminders via phone calls, text messages, or direct visits, and restrictions on access to new financing for members with arrears. Recovery measures include rescheduling, restructuring, and implementing a daily savings program to help ease members’ installment burdens. For members who are unable to fulfill their obligations, resolution is pursued through collateral execution or the application of the PPAP procedure in accordance with institutional operational standards. The study concludes that intensive communication, consistent supervision, and the application of prudential principles from the early stages of financing analysis are key factors in the successful management of non-performing financing.Keywords: Handling Efforts; Non-Performing Financing; Rahn; BMT. Penelitian ini bertujuan untuk menjelaskan upaya penanganan pembiayaan bermasalah pada produk Rahn di BMT Mandiri Sejahtera Cabang Dukun. Pembiayaan bermasalah menjadi isu penting karena dapat mengganggu stabilitas keuangan lembaga dan menurunkan tingkat kepercayaan anggota. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa penyebab utama pembiayaan bermasalah berasal dari kelemahan dalam proses survei dan analisis awal, serta faktor eksternal seperti kondisi ekonomi dan permasalahan rumah tangga anggota. Upaya penanganan dilakukan secara bertahap melalui pengawasan intensif terhadap pembiayaan yang berjalan, pemberian pengingat rutin melalui telepon, pesan singkat, dan kunjungan langsung, serta pembatasan akses pembiayaan baru bagi anggota yang memiliki tunggakan. Upaya penyelamatan dilaksanakan melalui penjadwalan ulang (rescheduling), restrukturisasi, dan penerapan program tabungan harian untuk membantu meringankan beban angsuran. Apabila anggota tidak mampu melunasi kewajibannya, penyelesaian ditempuh melalui eksekusi jaminan atau penerapan prosedur PPAP sesuai ketentuan operasional lembaga. Hasil penelitian menegaskan bahwa komunikasi yang intens, pengawasan yang konsisten, serta penerapan prinsip kehati-hatian sejak tahap analisis awal menjadi faktor utama dalam keberhasilan penanganan pembiayaan bermasalah.Kata Kunci: Upaya Penanganan; Pembiayaan Bermasalah; Rahn; BMT.